Stabilization of perfluoropolyethers (PFPEs) with acyl fluoride and carboxylic acid end-groups by UV-irradiation. (March 2019) - Saxena, Saurabh; Malik, Prateek; Tyagi, Ajay K.; Seshadri, Geetha; Mandal, Uttam Kumar
Abstract: Perfluoropolyethers (PFPEs) with acyl fluoride and carboxylic acid end-groups obtained by photo-oxidation of 1, 1, 2, 3, 3, 3-hexafluoro-1-propene (HFP) were subjected for ultraviolet (UV) stabilization. Effects of various stabilization parameters such as the type of lamp, lamp wattage, contact area and lamp distance on stabilization time, viscosity and molecular weight were studied in detail. High-pressure mercury vapor (HPMV) lamps and low-pressure mercury vapor (LPMV) lamps were used to carry out UV stabilization of unstabilized PFPEs. By increasing the lamp wattage, stabilization time decreased, but the weight loss of PFPEs increased. Among HPMV and LPMV UV lamps, LPMV lamps were more effective to carry out stabilization of PFPEs. Structural changes after UV stabilization were analyzed by FTIR and 19 F-NMR analysis. FTIR and NMR analysis confirmed the complete removal of the acyl fluoride group. Thermal stability of stabilized and unstabilized PFPEs was also studied by thermogravimetric analysis (TGA). Highlights: UV-irradiation is an effective method for fluorine end-capping of PFPEs. The acid value of PFPEs decreases drastically after UV stabilization. Molecular weight and viscosity of PFPEs increase after UV stabilization. Thermal stability of PFPEs increases after UV stabilization.